Overview Implementation of the First Pillar Community-Based Total Sanitation Program - Tuti Agustina; Darmawan Darmawan; Firman Firdauz Saputra; Fikri Faidul Jihad; Teuku Alamsyah (An Idea Health Journal, 2024)
Community-based total sanitation (STBM) is an approach aimed at changing hygiene and sanitation behaviour through empowerment of the community through sanitation techniques. When most members of the group stop pissing, it's called a piss stop. (BABS). By 2023, 194 villages in South Aceh district have been STBMkan, 21 of them have been Open Defacation Free (ODF), and 239 of them are not yet. The aim of this study is to find out how effective the first pillar STBM program is. Input, Process, Output, and Output are four parts of the research approach. The number of informants is six. The South Aceh Health Service conducted the study from November to December. This research is a type of qualitative research and is designed as an Evaluation Study Design. Research shows that the public is not participating in the implementation of the first pillar STBM program in the area of work of the Health Department of the Cabinet of South Aceh. The results show that the first pillar STBM program still has shortcomings and constraints in its implementation.